A pressure-state-response-support framework for assessing regional water environmental carrying status - Hu, Aqin; Li, Qingsheng (Frontiers in Environmental Science, 2022)
The water environment carrying status (WECS) is the embodiment of the ability of an aquatic ecosystem to maintain healthy and stable development; as such, it is an essential factor in the sustainable social and economic development of a region. This study aims to provide a framework for measuring the water environment carrying status of a region. Firstly, a new Pressure-State-Response-Support (PSRS) framework is proposed that fully embodies the supporting and restraining functions of the water environment regarding social and economic development. Secondly, a water carrying status index system containing 21 indicators is constructed based on this new PSRS model, and a water environment carrying status index (WECSI) is introduced to describe the WECS. Then, projection pursuit and entropy methods are used to calculate the WECSI. Based on the proposed PSRS framework and evaluation methods, eight cities along the Yangtze River in Jiangsu province were employed as examples, and their WECS was evaluated from 2012 to 2019. During the evaluation period the WECS of the eight cities improved to some extent, although several cities declined in some years; in those cities, the WECS ranking from highest to lowest was: Zhenjiang, angzhou, Wuxi, Changzhou, Taizhou, Nanjing, Nantong, and Suzhou. The five major influencing factors of these cities were pressure subsystems, inland water aquaculture areas, COD discharge of industrial sewage, the proportion of water quality above III in stream monitoring sections, greenery coverage rate of built-up areas, and ammonia nitrogen discharge in domestic sewage. The analysis indicated that appropriate improvement measures for the major influence factors would increase the WECS of each city, and thus government departments should commit to alleviating pressure and monitoring and supervising surface water quality while continuing to maintain a supporting force. Overall, the proposed framework and methodology is sound and effective for measuring the carrying status of regional water environments, and the method can provide guidance for the Ecological Environment Department.